Anaerobic Threshold Prediction Using the OMNI-Walk/Run Scale in Long-Distance Runners: A Preliminary Study - Campos, Y. A. C.; Vianna, J. M.; Guimarães, M. P.; Souza, H. L. R.; Domínguez, R.; Novaes, J. S.; Leitão, L. F. M.; Silva, S. F.; Reis, V. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To identify the anaerobic threshold through the lactate threshold determined by Dmax and rating of perceived exertion (RPE) threshold by Dmax and to evaluate the agreement and correlation between lactate threshold determined by Dmax and RPE threshold by Dmax during an incremental test performed on the treadmill in long-distance runners.